PENGARUH PENGENDALIAN INTERN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA DINAS KOTA PALANGKA RAYA) - Muhammad Gunawan; Yohanes Joni Pambelum; Rosel Rosel (Universitas Palangka Raya, 2021)
This study aims to provide an empirical explanation of the effect of internal control on the performance accountability of government agencies with leadership style as a moderating variable. The research method used in this research is descriptive statistical analysis, data instrument testing (validity and reliability tests), hypothesis testing, and determination coefficient test. The total population of this study consisted of 18 offices in the city of Palangka Raya using the census method, with the criteria set by the researcher, namely employees of the sub-planning, evaluation, reporting, and financial sections. at the Palangka Raya City Office, 60 people were sampled. The type of data used is primary data. The collected data were analyzed using IBM SPSS Statistics version 25. The results showed that the first hypothesis of internal control has an effect on the performance accountability of government agencies accepted. The second hypothesis of leadership style as a moderating variable strengthens the effect of internal control on the performance accountability of government agencies.